Functional and miRNA regulatory characteristics of INSIG genes highlight the key role of lipid synthesis in the liver of chicken (Gallus gallus) - Yaxin Yue; Ziming Liu; Ke Zhang; Qihui Jia; Dandan Wang; Zhang Wang; Yulong Guo; Donghua Li; Ruirui Jiang; Zhuanjian Li; Yadong Tian; Xiangtao Kang; et al. (Poultry Science, 2023)
ABSTRACT: The insulin-induced genes (INSIG1 and INSIG2) have been demonstrated to play a vital role in regulating lipid metabolism in mammals, however the function and regulation mechanism of them remains unknown in poultry. In this study, firstly the phylogenetic trees of INSIGs among various species were constructed and their subcellular locations were mapped in chicken LMH. Then the spatiotemporal expression profiles, over-expression and knockdown assays of chicken INSIGs were conducted. Furthermore, conservation of potential miRNA binding sites in INSIGs among species were analyzed, and the miRNA biological function and regulatory role were verified. The results showed that chicken INSIGs located in cellular endoplasmic reticulum, and were originated from the common ancestors of their mammalian counterparts. The INSIGs were widely expressed in all detected tissues, and their expression levels in the liver of chicken at 30 wk were significantly higher than that at 20 wk (P < 0.01). Over-expression of INSIGs led no significant increase in mRNA abundance of lipid metabolism-related genes and the contents of triacylglycerol (TG) and cholesterol (TC) in LMH cells. Knockdown of INSIG1 led to the decreased expressions of ACSL1, MTTP-L, ApoB, ApoVLDLII genes and TG, TC contents (P < 0.05). Knockdown of INSIG2 could significantly decrease the contents of TG and TC, and expressions of key genes related to the lipid metabolism (P < 0.05). Moreover, INSIG1 was directly targeted by both miR-130b-3p and miR-218-5p, and INSIG2 was directly targeted by miR-130b-3p. MiR-130b-3p mimic and miR-218-5p mimic treatment could significant decrease the mRNA and protein levels of INSIGs, mRNA levels of genes related to lipid metabolism, and the contents of TG and TC in LMH cells. The inhibition of miR-130b-3p and miR-218-5p on TG and TC contents could be restored by the overexpression of INSIGs, respectively. No significant alteration in expressions of sterol regulatory element binding protein (SREBPs) and SREBP cleavage-activating protein (SCAP) were observed when INSIGs were over-expressed. SCAP was down-regulated when INSIG1 was knocked down, while SREBP1 was down-regulated when INSIG2 was knocked down. Taken together, these results highlight the role of INSIG1 and INSIG2 in lipid metabolism and their regulatory mechanism in chicken.